Applied mechanics reviews. - American Society of Mechanical Engineers (New York American Society of Mechanical Engineers, 1948)
"An international review journal in the engineering sciences." Also distributed by the United States Government Printing Office to depository libraries as part of the Air Force Office of Scientific Research (AFOSR) series. Includes seperate indexes.
Keywords: Mechanics, Applied -- Abstracts -- Periodicals